Combined effects of irrigation level and fertilization practice on yield, economic benefit and water-nitrogen use efficiency of drip-irrigated greenhouse tomato - Wu, You; Yan, Shicheng; Fan, Junliang; Zhang, Fucang; Zhao, Wenju; Zheng, Jing; Guo, Jinjin; Xiang, Youzhen; Wu, Lifeng (Agricultural water management, 2022)
The over-application of irrigation and chemical fertilization in the greenhouse vegetable production system (GVPS) in China can jeopardize fruit quality, compromise economic profit and waste resources. Seeking optimal water and fertilizer supply mode for GVPS is urgently required to improve resource use efficiency and economic benefit. A greenhouse experiment was conducted during four consecutive tomato growing seasons to investigate the combined effects of various irrigation levels and fertilization practices on yield, fruit quality, economic benefit, water use efficiency (WUE) and nitrogen use efficiency (NUE) of drip-fertigated tomato, and to obtain the optimal water and fertilizer supply practice by the principal component analysis (PCA). On the basis of full irrigation (W1: 100%ETc, ETc was the crop evapotranspiration), two deficit irrigation levels (W2: 75%ETc, W3: 50%ETc) were set. Except for the conventional fertilization practice used by local farmers (CC: chicken manures for basal application and chemical fertilizer for topdressing), four other fertilization practices were considered, including soluble organic fertilizers for topdressing (SO), soluble chemical fertilizers for topdressing (SC), both soluble organic and chemical fertilizers for topdressing (SOSC), and a control with no fertilizer application under full irrigation (CK). The results showed that SOSC obtained relatively high plant nitrogen uptake, net profit and WUE, and significantly improved tomato yield. Organic fertilizers addition reduced nitrate content in tomato fruits. Deficit irrigation promoted CC to obtain higher WUE than SC. According to the result of PCA, the comprehensive ranking of SOSC was first among the fertilization practices, regardless of irrigation levels and growing seasons. W1SOSC and W2SOSC were highly recommended for greenhouse tomato production in spring and autumn seasons, respectively. ●Drip irrigation and fertilization effects on yield and economic benefit of tomato were explored.●Organic fertilizers addition reduced nitrate content in tomato fruits.●The comprehensive ranking of soluble organic and chemical fertilizers for topdressing was first.●Soluble organic and chemical fertilizers combined with full irrigation or 75% full irrigation was recommended.